Rare earth elements (REE) as a tracer for redox conditions in methane-seep carbonates at continental margins (2025)
Cold seep formations are a main feature in continental margins where methane-rich fluids migrate to the seawater column through the sediments. These mechanisms of methane seepage allow the precipitation of carbonates in the sub-seafloor sediments by the anaerobic oxidation of methane (AOM). This process is the result of the symbiosis between chemosynthetic sulfate reducing bacteria, and methane oxidizing archaea. To test the redox conditions that are moved by these dynamics, rare earth element (REE) patterns in aragonite seep carbonates from the Gulf of Mexico (GoM) in localities AC645 and GC232, and from the South China Sea (SCS) in localities Haima and Site F, have been studied. The δ¹³C values for the SCS (ranging from -37.97 to -50.05‰) are lower than those from the GoM ranging from -20.63 to -30.57‰), indicating more oxic conditions. REE normalized patterns show a negative cerium (Ce) anomaly for aragonites in AC645 and a positive Ce anomaly for Haima suggesting a variation in redox conditions between continental margins. All samples show a positive europium (Eu) anomaly that is related to asphalt volcanism in the GoM and to microbial activity in the SCS, establishing different methane sources (thermogenic and biogenic respectively). Finally, temporal changes in redox mechanisms were inferred, suggesting changes in the seepage intensity and migration of the redox horizon at each cold seep locality.